2015
DOI: 10.1016/j.pain.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of the same drug

Abstract: Several studies have shown that psychological factors such as learning, expectation, and emotions can affect pharmacological treatment and shape both favorable and adverse effects of drugs. This study investigated whether nocebo information provided during administration of an analgesic cream could reverse topical analgesia to hyperalgesia. Furthermore, we tested whether nocebo effects were mediated by negative emotional activation. A total of 142 healthy volunteers (73 women) were randomized into 6 groups. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 33 publications
5
40
0
3
Order By: Relevance
“…Fig. 4 shows the results of this search, in which only seven studies were found to have used one of these designs in placebo analgesia (Aslaksen, Zwarg, Eilertsen, Gorecka, & Bjørkedal, 2015; Atlas et al, 2012; Berna et al, 2017; Butcher & Carmody, 2012; Kam-Hansen et al, 2014; Lund, Vase, Petersen, Jensen, & Finnerup, 2014; Schenk, Sprenger, Geuter, & Buchel, € 2014). …”
Section: Current Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…Fig. 4 shows the results of this search, in which only seven studies were found to have used one of these designs in placebo analgesia (Aslaksen, Zwarg, Eilertsen, Gorecka, & Bjørkedal, 2015; Atlas et al, 2012; Berna et al, 2017; Butcher & Carmody, 2012; Kam-Hansen et al, 2014; Lund, Vase, Petersen, Jensen, & Finnerup, 2014; Schenk, Sprenger, Geuter, & Buchel, € 2014). …”
Section: Current Evidencementioning
confidence: 99%
“…Four of the seven studies used the balanced placebo design (Aslaksen et al, 2015; Butcher & Carmody, 2012; Kam-Hansen et al, 2014; Schenk et al, 2014), while two used the balanced open-hidden design (Atlas et al, 2012; Lund et al, 2014). The final study conducted by Berna et al (2017) used a novel design here described as a “balanced active placebo design.” In this variation of the balanced placebo design, receipt of an active treatment or placebo are factorially crossed with administration of an active placebo or placebo, with the second factor replacing the instructions of treatment allocation typical of the balanced placebo design.…”
Section: Current Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, placebo and nocebo effects can substantially modulate the efficacy and tolerability of active pharmacological or other medical treatments [15, 16]. This empirical evidence from experimental and clinical studies challenges health-care professionals to translate and implement the findings of placebo and nocebo research into practice.…”
Section: Introductionmentioning
confidence: 99%